KERINDUAN PADA NARATIF Pola Retorika Komunikasi Politik Capres dan Cawapres THE YEARNING FOR NARATIVE The Pattern of Political Communication Rhetorics of President Candidates and Vice President Candidates - Prisgunanto, ilham (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
Have  you   been  boring   with  pattern    of  rhetorics  political    Communications presidents   candidate  and vice presidents  candidate  in this election campaign?  It  . is  true  that political   communications    rhetorics  presidens    candidate   and  vice presidents   candidate  only majoring  element  of argumentatif   not narrative.  As a result  that Election  of Pilpres  20()9fully  of falsehood,  deception  and betrayal  to voter.  Exactly  voter fully  hope patterns  of narrative  in political  communications rhetorics   with a  which  big  swcy.  Its proof   of  Voter swayed   by buttonhole   of Celebrities   in legislative  election  then which assumed  can  make their better  life. This condition  show political  life pattern  Indonesia move  to instan models.